2015
DOI: 10.1002/cbin.10499
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian target of rapamycin signaling pathway regulates myocyte enhancer factor‐2C phosphorylation levels through integrin‐linked kinase in goat skeletal muscle satellite cells

Abstract: Mammalian target of rapamycin (mTOR) signaling pathway plays a key role in muscle development and is involved in multiple intracellular signaling pathways. Myocyte enhancer factor-2 (MEF2) regulates muscle cell proliferation and differentiation. However, how the mTOR signaling pathway regulates MEF2 activity remains unclear. We isolated goat skeletal muscle satellite cells (gSSCs) as model cells to explore mTOR signaling pathway regulation of MEF2C. We inhibited mTOR activity in gSSCs with PP242 and found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Despite considerable interest, it remains unclear how mTOR signals to establish early steps of myogenic commitment in muscle stem cells. Multiple genetic studies and our data in Figure 4E suggest the requirement of the Raptor-containing mTOR complex 1 (mTORC1), but not the Rictor-containing mTORC2 to mediate the early steps of myogenic commitment (Bentzinger et al, 2008;Hung et al, 2014;Rodgers et al, 2014;Wan et al, 2006;Wu et al, 2015). One of the major substrates of mTORC1, p70S6K1 is dispensable for the early steps of the myogenesis program ( Figure 4E and (Ge and Chen, 2012;Ohanna et al, 2005)).…”
Section: Discussionmentioning
confidence: 91%
“…Despite considerable interest, it remains unclear how mTOR signals to establish early steps of myogenic commitment in muscle stem cells. Multiple genetic studies and our data in Figure 4E suggest the requirement of the Raptor-containing mTOR complex 1 (mTORC1), but not the Rictor-containing mTORC2 to mediate the early steps of myogenic commitment (Bentzinger et al, 2008;Hung et al, 2014;Rodgers et al, 2014;Wan et al, 2006;Wu et al, 2015). One of the major substrates of mTORC1, p70S6K1 is dispensable for the early steps of the myogenesis program ( Figure 4E and (Ge and Chen, 2012;Ohanna et al, 2005)).…”
Section: Discussionmentioning
confidence: 91%
“…The unique protein structure enables ILK to play an important role in the coordination of extracellular matrix (ECM) and the signal transduction of growth factor [ 28 , 29 ]. Evidence suggests that ILK may directly phosphorylate proteins associated with tumorigenesis by increasing cell proliferation, enhancing anchor independence of growth factors, and inhibition of apoptosis [ 14 , 30 , 31 ]. Investigations also revealed that MEF2C phosphorylation level increased significantly after ILK inhibition and knocking down, and the MCK expression that plays a vital role in the proliferation and differentiation of muscle cells increased significantly, suggesting that MEF2C transcription increased significantly after ILK inhibition or knocking down.…”
Section: Discussionmentioning
confidence: 99%
“…ILK regulates the phosphorylation of Akt at Ser473 and of glycogen synthase kinase 3 (GSK3) in various cell types [ 13 ]. We found that ILK also directly regulates MEF2C phosphorylation in the skeletal muscle cells of goats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, samples containing 1-3 mg total protein were precleared with Protein A/G Sepharose for 30 min. The cleared lysates were incubated with 4 mg anti-Tβ4 at 4 • C for at least 2 h, and up to overnight [37].…”
Section: Co-immunoprecipitation (Co-ip)mentioning
confidence: 99%